Swenson-like pull-through for treatment of the rare association between Hirschsprung’s disease and anorectal malformation - Mohamed Abdelmalak; Mohamed Mansy; Hazem Khafaga; Yasmine Ghazaly; Reem Saeed; Nada Yakout; Saber Waheeb; Mostafa Zain (BMC Pediatrics)
Abstract Background Anorectal malformations and Hirschsprung’s disease are congenital conditions impacting the digestive system, with a particularly uncommon co-occurrence, estimated at 2–3% of all ARM cases. This case series explores this rare association through three distinct cases, each presenting unique clinical challenges and insights. Methods We report a series of five patients with ARM who were concurrently diagnosed with HD based on clinical and radiological evaluations, with definitive confirmation obtained through rectal biopsy. In cases where HD was diagnosed after the complete surgical repair of ARM, the patients underwent a Swenson-like pull-through procedure. Notably, the anastomosis was created approximately 3 cm from the anal verge, rather than the conventional 3 cm from the dentate line. Results This study reviewed the records of 136 ARM patients treated at our center over five years, identifying five cases with concurrent HD. In three of these cases, HD was initially overlooked and diagnosed only after ARM repair. These patients underwent a Swenson-like pull-through procedure. During follow-up, two patients achieved good bowel control without fecal soiling, while the third had regular bowel movements and satisfactory growth, albeit with occasional episodes of enterocolitis managed medically. The remaining two cases were identified earlier, following colostomy, which led to a different management approach. Conclusion This case series underscores the critical importance of considering HD in patients with ARM who present with persistent, atypical gastrointestinal symptoms post-surgical repair of their ARM. Preservation of the aganglionic neoanal canal with a subsequent Swenson pull-through appeared beneficial to achieve good postoperative continence.